2018
DOI: 10.1016/j.physb.2017.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement induced shift in energy band edges and band gap of a spherical quantum dot

Abstract: We have proposed and validated an ansatz as effective potential for confining electron/hole within spherical quantum dot in order to understand quantum confinement and its consequences associated with energy states and band gap of Spherical Quantum Dot. Within effective mass approximation formalism, considering an ansatz incorporating a conjoined harmonic oscillator and coulomb interaction as the effective potential for confining an electron or a hole within a spherical quantum dot and by employing appropriate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 79 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…The excited electron returns to the ground state and associating with the hole, then, the fluorescence of the QDs is generated. Due to quantum confinement effects, the energy of the emitted photon is determined by the crystalline dimension of the QDs [7]. By using various methods or employed Cd and Se precursors, many researchers have attempted to synthesise the CdSe QDs.…”
Section: Introductionmentioning
confidence: 99%
“…The excited electron returns to the ground state and associating with the hole, then, the fluorescence of the QDs is generated. Due to quantum confinement effects, the energy of the emitted photon is determined by the crystalline dimension of the QDs [7]. By using various methods or employed Cd and Se precursors, many researchers have attempted to synthesise the CdSe QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a red shift trend occurred in MoSSe QDs as related to bulk components with the confined absorption peak of 450 nm. The cases suggested that the dimension declined introduced the quantum confinement effect in the band gap of photocatalysts, with altered photocatalyst absorption features. , No apparent pronounced change in the absorption edges of MoSSe was noticed when Se was presented, implying that the Se was combined through the surface of QDs relatively rather than doping. As well as, the absorption intensity of MoSSe QDs has pronounced, and the absorption in visible light range expands broader rather than adding to the Se, which is responsible for the broad-spectrum light absorption response of Se .…”
Section: Resultsmentioning
confidence: 99%
“…CoO@meso-CN@MoS2 material presented an energy gap between 2.87 and 2.88 eV, while the band gap between bulk MoS2 was 1.81 eV. It is recognized that the quantum confinement effects and the coefficient reaction to nanostructure CoO@meso-CN contributed to the bandgap increment [13]. The UV-Vis spectra result displays the propriety of the CoO@meso-CN@MoS2 heterostructure hybrids with a visible light sensitive photocatalyst.…”
Section: Optical Properties Analysismentioning
confidence: 92%